Skleritis dan Rheumatoid Arthritis - Cut Karel Dithia; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Rheumatoid arthritis is the result of a chronic inflammatory process that involves the immune system. One of the antibodies that is often detected in RA and scleritis patients is rheumatoid factor (RF). RF are antibodies produced by the immune system to attack the body's own tissues, including joints and synovial membranes. Another part of the antibody effect that is cyclic anti-citrate antibody (Anti-CCP), is an antibody that recognizes citrulinating proteins in body tissues, namely certain protein modifications that occur in RA patients and are considered as important factors in the pathogenesis of this disease. Increased RF levels can occur in patients with RA as well as in patients with scleritis. Scleritis is an inflammatory condition of the sclera, which is the thick white layer that lines the front of the eyeball. The etiology or cause of scleritis is still not known with certainty, apart from uncertain etiology, there are factors that can increase the risk of developing scleritis, such as autoimmune diseases, infections, vascular disorders, trauma, and drugs. This literature review discusses the relationship between rheumatoid arthritis and scleritis.